PERENCANAAN ARSITEKTUR ENTERPRISE PADA PENYEMPURNAAN APLIKASI SITMAPAS RUMAH SAKIT KRAKATAU MEDIKA - Boy Muhammad Ridwan; Roy Amrullah Ritonga; Anita Megayanti (Program Studi Sistem Informasi, Universitas Banten Jaya, 2022)
SITMPAS is a Patient Management Information System used by Krakatau Medika Hospital, Cilegon. The features in SITMAPAS include patient administration, Outpatient, Inpatient, Operative Medical Support, Non Operative Medical Support, Service Support, Pharmacy and Medical Records, and Logistics. Some of these features are often disturbed and some functions are not in accordance with user needs, resulting in disrupted service processes, due to the absence of development planning in advance in the face of the current industrial 4.0 era. With these problems, this study aims to design architecture from the business, data, application and technology side using the TOGAF ADM method. The use of the TOGAF ADM method will produce a blueprint document for information architecture systems in the development of information systems to support the needs of the Krakatau Medika Hospital. The application of the TOGAF Architecture Development Method (ADM) method is able to identify needs so that it can analyze Fit/Gap and evaluate the SITMAPAS application business process and can propose an imperfect business process, namely the New KHS to produce better performance in targeting organizers from Krakatau Medika.